PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL DENGAN MENGGUNAKAN APLIKASI POWER DIRECTOR - Holip, Zulahmad; Darmawati, Gusnita; Yuspita, Yulifda Elin; Annas, Firdaus (Information Technology Education Department, 2025)
Learning media plays an important role as a tool in facilitating the teaching and learning process. The use of learning media is essential in simplifying complex concepts, such as electrical energy circuits, to increase students' engagement and interest in science subjects. This study uses a Research and Development (R&D) methodology that aims to design and produce audiovisual-based learning media for integrated science subjects on the topic of “electrical energy circuits” for grade VI students at SDN 20 Limo Balai. The developed learning media is designed to improve the efficiency and effectiveness of the learning process in science education in elementary schools. The research findings show that the audiovisual-based learning media significantly supports teachers and students in the teaching and learning process. The media achieved a validity score of 0.56, categorized as valid, a practicality score of 0.87, indicating that the media is very practical, and an effectiveness score of 0.77, which is categorized as effective. These results indicate the high feasibility and suitability of the developed media as a science learning aid in elementary schools.